SCIENTIFIC LITERACY SKILLS OF PRE-SERVICE BIOLOGY TEACHERS BASED ON SPENT YEARS IN UNIVERSITY AND CONTRIBUTED FACTORS - Widi Cahya Adi; Muhammad Saefi; Ndzani Latifatur Rofi'ah (BIOEDUKASI, 2020)
Apart from the importance of scientific literacy for the pre-service teachers as the key to success in becoming a teacher who can teach and make literate students, not many studies have revealed the contributing factors, especially the learning experience students. This study aims to measure the level of scientific literacy skills of pre-service students and contributed factors. One hundred and five students at state Islamic universities in Indonesia participated in this study. The data were collected in three stages. First, the level of scientific literacy skills using the Test of Scientific Literacy (TOSLS). Two students with the highest and lowest abilities in each batch were interviewed. Finally, the semester learning plan (RPS) and practicum instructions are reviewed. The mean was used to describe the level of scientific literacy skills, and one-way ANOVA to test differences in skill between the four groups based on the spent year in university. Data obtained from interviews and analysis were analyzed using content analysis techniques. As a result, pre-service biology teachers have a "medium" level of scientific literacy skills. There was a difference between the four groups with the highest and most significantly different fourth-year students. The primary cause of scientific literacy skills is the student learning experience in terms of learning strategies, assignments, evaluations, and practicums activities that are obtained by pre-service biology teachers. The results suggest the following implications for teaching: faculties must identify scientific literacy skills and carry out learning with learning strategies, assignments, evaluations, and practicum activities that support the growth of scientific literacy abilities of a pre-service biology teacher.